Differences in Poly(ADP-ribose) Polymerase1- (PARP1-) and Proliferative Cell Nuclear Antigen (PCNA) Immunoreactivity in Patients Who Experienced Successful and Unsuccessful Microdissection Testicular Sperm Extraction Procedures - Akarsu, Süleyman; Büke, Baris; Gürgen, Seren Gülsen; Akdemir, Serkan; Gode, Funda; Biçer, Merve; Tekindal, Mustafa Agah; Isik, Ahmet Zeki (Urology Journal, 2017)
Purpose: The aim of this study is to evaluate expression of deoxyribonucleic acid (DNA) synthesis and repair markers in testicular tissues of azoospermic men in whom sperm retrieval could and could not be achieved as a result of microdissection testicular sperm extraction (micro-TESE) procedure. Materials and Methods: In this prospective cohort study, testicular tissues were retrieved from 60 Non-obstructive Azoospermia (NOA) patients who underwent micro-TESE procedure. These patients were divided into two groups: micro-TESE positive group, which included 30 NOA patients from whom sperm could be extracted via micro-TESE procedure; and micro-TESE negative group, which included 30 NOA patients from whom sperm retrieval could not be achieved via micro-TESE procedure. Expression and distribution patterns of poly(ADP-ribose) polymerase-1 (PARP-1) and proliferative cell nuclear antigen (PCNA) in extracted tissues were assessed by immunohistochemical staining to reveal any differences in DNA synthesis and repair between the two groups. Results: Micro-TESE positive group exhibited significantly stronger immunoreactivity for both PCNA and PARP-1 (P = .001 and P = .001 respectively). The results of this study reveal that both DNA synthesis and repair markers were expressed strongly in patients who experienced successful micro-TESE procedure. Conclusion: Although further studies are needed to support these findings, PARP-1 and PCNA expression in testicular tissues of NOA patients could be promising predictive factors for micro-TESE procedure success.